Video diaries: a discussion of their use for researching the learner experience in higher education. (2015) - Jefferies, Amanda
This paper considers the rationale for using video diaries as a method of qualitative data gathering for research into students' experiences of higher education (HE). In particular, the paper considers how video diaries have been employed for researching students' views and attitudes to their own learning and development. The paper examines the literature on the purpose of reflective video diary research as the method has moved beyond its initial primary development in medical research and specifically into their use in HE. The particular benefits of personal video-diary compilation are considered in terms of the autonomy of the participant. A methodology for employing video diaries as a research method for data collection is discussed within the context of three case studies with undergraduate students at a UK university. The conclusions highlight the unique value of participant-generated video diaries for researching the nature of the student learning experience in HE.